[PP.14.29] ALERT REACTION DURING VASCULAR NON-INVASIVE EVALUATION: WHAT ARE WE MEASURING?. (September 2017) - Gonzalez, S.; Martinez, G.; Ricon, D.; Mendez, M.; Diganchi, O.; Donaire, J.; Schiavone, M.; La Greca, R.; Ramella, I.
Abstract : Objective: a-To determine associations between office and alert-BP component during vascular non-invasive evaluation, according to age groups. b-To evaluate hemodynamic mechanisms associated with alert-BP. C-To determine prevalence of alert-BP significantly elevated in each group. Design and method: 168 patients were prospectively evaluated. After applying exclusion criteria (age below 18/above 80 years, secondary hypertension, heart diseases), 158 treated-hypertensives were included. Supine BP was measured (three determinations during five minute rest) prior to non-invasive vascular evaluation, that included: 1-Impedance Cardiography, with evaluation of cardiac index (CI), vascular resistance index (VRI), and thoracic fluid content (TFC); and 2-Tonometric PWV. Finally, 24 hours ABPM was placed. Alert-BP was defined as the difference between office systolic-BP and diurnal systolic-BP in ABPM (a-SBP). The population was sub-classified according to age in two groups: below 50 (A) and above 50 years (B). Associations between office-SBP and a-SBP were done. Univariate correlations between a-SBP and CI, VRI, TFC and PWV were performed (Pearson). High a-SBP (above 1DS of a-SBP mean value) was defined and the prevalence determined in each group. Results: Two groups emerged: A (n = 58, 41 ± 7 years, 138 ± 15/89 ± 9 mmHg, 45.4% females) and B (n = 108, 63 ± 6 years, 143 ± 16/85 ± 10 mmHg, 47.0% females). Direct associations between office-SBP and a-SBP were found (A: r = 0.61, p = 0.0001 and B: r = 0.69, p = 0.0001). In A only CI was correlated with a-SBP (r = 0.31, p = 0.028). In B-group, both CI and PWV were directly correlated with a-SBP (r = 0.23, p = 0.01 and r = 0.23, p = 0.019, respectively). VRI and TFC were not associated with a-SBP in both groups. High a-SBP resulted in >26 mmHg. The prevalence of High a-SBP was higher in B group (23.1% vs 6.38% in A, p = 0.016). Figure. No caption available. Conclusions: Alert-SBP component had a strong association with office-SBP, being ostensible in maturity and old age. In young people was directly related to cardiac output, while those over 50 years showed linear relationships with cardiac output and arterial stiffness. Therefore, the hemodynamic evaluation in adults with elevated office-SBP may be partially affected by dynamic factors, with overestimation of some physiological parameters dependent of BP, as pulse wave velocity.